Pengaruh Faktor Internal Dan Eksternal Terhadap Kinerja Perbankan Pada Bank Umum Yang Terdaftar Di Bursa Efek Indonesia - Walad Wirawan; Jufrizen Jufrizen; Muis Fauzi Rambe (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The rapidly growing of infrastructure development in Indonesia is oneof the financial institutions financing target, especially bankinginstitutions. Banking industry has high level of competition, and needsto perform extremely well in order to be the leader of theirbusiness.This research aims to know the effect of internal factors andexternal factors on bank’s performance at commercial banks category 4(BUKU 4) that listed in Indonesian Stock Exchange.This research usesasosiative method with purposive sampling in order to collect thesecondary datas. Those datas are analyzed using multiple linierregression analysis by SPSS 24. The result of this research shows thatCapital Adequacy Ratio (CAR), Non-Performing Loan (NPL), andinflation rate have significant impact, meanwhile Loan to Deposit Ratio(LDR),Gross Domestic Product (GDP) growth rate, and BI Rate havenon-significant impact on Return on Asset (ROA), which can descibesbetter on this regression model: ROA = -5,055 + 0,308CAR +0,022LDR - 1,516NPL + 0,187IHK – 0,052PDB + 0,061BIR.Therefore,banks need to pay more attention at CAR, LDR, NPL, inflation rate,GDP growth rate, and BI Rate in running their business in order toarchieve better profitability.